2016
DOI: 10.2174/1874364101610010119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Public Child Eye Health Tertiary Facility for Pediatric Cataract in Southern Nigeria I: Visual Acuity Outcome

Abstract: Purpose:A retrospective study of the outcome of congenital and developmental cataract surgery was conducted in a public child eye health tertiary facility in children <16 years of age in Southern Nigeria, as part of an evaluation.Materials and Method:Manual Small Incision Cataract Surgery with or without anterior vitrectomy was performed. The outcome measures were visual acuity (VA) and change (gain) in visual acuity. The age of the child at onset, duration of delay in presentation, ocular co-morbidity, non oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…This is consistent with findings from other studies [6,12,14]. Duke on the other hand, reported that congenital cataract was the most common type of cataract in his study [15]. Furthermore, this study established that children's visual outcome was associated with the timing of refraction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with findings from other studies [6,12,14]. Duke on the other hand, reported that congenital cataract was the most common type of cataract in his study [15]. Furthermore, this study established that children's visual outcome was associated with the timing of refraction.…”
Section: Discussionsupporting
confidence: 91%
“…As for postoperative complications, this study found that they were less post-operative complications (29.1%) with anterior segment being the most common complications (15.4%), followed by posterior segment (9.4%) and a combination of both anterior and posterior segment (4.3%) respectively. Duke [15] also had less postoperative complication of only nine out of hundred and thirty-two participants (6.8%). According to these results, there is less likelihood of children achieving good visual outcomes after surgery if they encountered complications, intraoperatively or postoperatively.…”
Section: Discussionmentioning
confidence: 91%
“…5,10 The visual acuity results of the vision were not influenced by gender differences, the poor results of visual acuity could be caused by the presence of amblyopia that had exceeded the critical period added by the presence of Nystagmus. 14,15 The average number of operated children in India was 9 years old with a follow-up of 3 to 8 years, 149 children had BCVA >6/18. Many factors influence, among others: cataract type, type of surgery, intraocular lens type, age of operation, presence or absence of postoperative uveitis, and pre-operative visual acuity.…”
Section: Discussionmentioning
confidence: 99%